-33=2+5y

Simple and best practice solution for -33=2+5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33=2+5y equation:


Simplifying
-33 = 2 + 5y

Solving
-33 = 2 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
-33 + -5y = 2 + 5y + -5y

Combine like terms: 5y + -5y = 0
-33 + -5y = 2 + 0
-33 + -5y = 2

Add '33' to each side of the equation.
-33 + 33 + -5y = 2 + 33

Combine like terms: -33 + 33 = 0
0 + -5y = 2 + 33
-5y = 2 + 33

Combine like terms: 2 + 33 = 35
-5y = 35

Divide each side by '-5'.
y = -7

Simplifying
y = -7

See similar equations:

| 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 | | .4(12n-8)=26 | | 4(2x-7)=3(x+4) | | 2b+12b=70 | | 13x+(x+3)+(x+2)+(x+7)=40 | | 6x^3-5x^2+1=0 | | -3x-14+10x=-2 | | -6(v+7)=9v+48 | | 2(3x+8)+6(x-1)=-12 | | 5x-4+3x=6x+4(2-x) | | 8-5x=-29 | | (5n^2+11)-(3n^2+6)= | | -3.4m=47.6 |

Equations solver categories